Mutual antimicrobial effect of hibiscus acid and nalidixic acid against multidrug-resistant foodborne bacteria in CD-1 mice - Rangel-Vargas, Esmeralda; Falfan-Cortés, Reyna N; Torres-Vitela, Ma Refugio; Portillo-Torres, Lizbeth A; Gómez-Aldapa, Carlos A; Guzmán-Ortiz, Fabiola A; Castro-Rosas, Javier (The Journal of Infection in Developing Countries, 2025)
Introduction: The antimicrobial effect of hibiscus acid (HA) alone and in combination with nalidixic acid (NA) on multi-antibiotic-resistant Shiga-like toxin-producing Escherichia coli (STEC) and Salmonella Typhimurium (ST) was evaluated in CD-1 mice. Methodology: The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) for NA and HA were determined against both STEC and ST. Fifteen sets of 6 mice each were utilized: 6 groups were exposed orally to 5 log10 colony forming units of a pool of 3 ST strains, another 6 were exposed to a pool of STEC; and 3 acted as controls. Six hours post-inoculation, specific mice groups received either oral solutions containing HA (2 and 7 mg/mL), or NA (20 and 250 µg/mL), or HA/NA (2 mg/mL HA and 20 µg/mL NA), or isotonic saline. All mice were euthanized on day 5 post infection, and tissues were collected to analyze the numbers of bacteria. Results: The study determined the MIC and MBC of 7 mg/mL HA; 150 and 250 µg/mL of NA; and two concentrations of HA/NA (1 mg/mL/5 µg/mL and 2 mg/mL/20 µg/mL). Mice that were infected and treated with HA at 7 mg/mL or with HA/NA (2 mg/mL/20 µg/mL) did not have STEC or ST in their fecal samples or in the tissues. However, the pathogens were present in the stool and tissues of infected and untreated mice, and those infected and exclusively treated with NA250, NA20, or HA2 mg/mL. Conclusions: HA is an alternative for the treatment against antibiotic-resistant pathogenic bacteria.